Hakikat Musik Sekular dan Musik Gereja: Kajian Ontologis dari Perspektif Teori Idealisme Plato - Michael Hari Sasongko (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2023)
In essence, secular music is different from church music. Secular music is the music industry, which built on the basis of a capitalistic system. Secular music is created and performed for the glory and benefit of the composer or singer himself. That is the reason secular is called worldly music. Not so with church music. The subject, goal, and message of church music is the person of Jesus Christ himself, so this music is spiritual. Based on Plato’s theory of idealism (which s related to Plato’s theory of the soul), it can be said that secular music is in the area of ephitumia and thumos, while church music is in area of logostikon. Secular music leads to something that is not eternal while the church music is directed to eternal goals. The goal of church music is ultimately divine intellect; rational but faithful.